2015
DOI: 10.3109/13880209.2015.1059861
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and anthelminthic activities of a novel dichapetalin and other constituents ofDichapetalum filicaule

Abstract: This is the first report of the phytochemical investigation of D. filicaule. The study has yielded a new dichapetalin and also demonstrated the potential anthelminthic properties of the constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 38 publications
4
34
0
1
Order By: Relevance
“…Chemical constituents of Dichapetalum filicaule were isolated and tested for anthelmintic activity on a Necator americanus egg hatch inhibition assay. Three compounds (including a new dichapetalin) were found to be active: dichapetalin X, dichapetalin A and glycerol monostearate [71].…”
Section: Natural Products Active Against Intestinal Parasitic Nematodesmentioning
confidence: 99%
“…Chemical constituents of Dichapetalum filicaule were isolated and tested for anthelmintic activity on a Necator americanus egg hatch inhibition assay. Three compounds (including a new dichapetalin) were found to be active: dichapetalin X, dichapetalin A and glycerol monostearate [71].…”
Section: Natural Products Active Against Intestinal Parasitic Nematodesmentioning
confidence: 99%
“…1D-NMR data coulped with 2D-NMR data (HSQC and HMBC) of 6 corresponded to a well-known triterpenoid, namely pomolic acid. [20][21][22] 1D-NMR revealed that compound 6 contained five methyl, one methine carbinol, one olefinic bond, one carbonyl carbon, and remaining aliphatic methines and methylenes. Hydroxygenation occurred at carbon carbinol C-3 (δ C 80.1) with the key HMBC correlations H-1, H-23, and H-24/C-3.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…[8][9][10] Bioactive dichapetalins and several other compounds have been isolated from Dichapetalum species. [11][12][13][14][15][16] Dichapetalum gelonioides (Roxb.) Engl (Figure 1) is a large shrub or small tree with pubescent branchlets and found distributed in evergreen and semi-evergreen forests as forest undergrowth.…”
Section: Introductionmentioning
confidence: 99%